Pengaruh Variasi Produk dan Cita Rasa Terhadap Kepuasan Konsumen HokBen Royal Plaza Surabaya - Amalia, Farach Annisa (Research Journal of Social Science and Economics, 2025)
This HokBen fast food restaurant is one of the restaurants that is in great demand by many Indonesian people, especially Surabaya, because basically people nowadays need food that is fast and practical to serve, and like food with an authentic taste, like HokBen which has unique food characteristics. provides a wide variety of product variations with a different taste with other fast food restaurants. This is due to the suitability of fast food with Indonesian cultural tastes, namely being able to choose according to customer needs. This study aims to determine and analyze the effect of the diversity of Product Variations, and Taste on Consumer Satisfaction HokBen Royal Plaza Surabaya. The type of research used is quantitative research. The sampling technique used purposive sampling technique. The data collection method is using a questionnaire. The results showed that product variety and taste have a significant influence on consumer satisfaction. Product variation variables, which include product completeness, product brand, product size variation, and product quality, have an important role in satisfying customer expectations. The more diverse the products offered, the more likely consumers are to be satisfied with the expected product. In addition, taste is also a factor that is measured in terms of taste, smell and mouth feeling felt by consumers, has a significant influence on consumer satisfaction. Consumers tend to choose products with good quality that can meet their needs. This research contributes to understanding the importance of product variety and taste in the context of consumer satisfaction. The findings of this study can be used by franchise companies to plan a marketing strategy that is effective and acceptable to consumers, including developing various product brands and maintaining consistent product quality.